Teologiee as gevaarlike mensemaaksels: Burton Mack se evaluasie van vroeg-Christelike mites - Strijdom, Johan ca. 21. Jh. (Hervormde teologiese studies, 1997)
Theologies as dangerous human constructs: Burton Mack's evaluation of early Christian myths. After an introductory explication of the social approach to myths/theologies and a consideration of the ethical urgency for such a humanistic strategy, this article offers a systematic survey of Burton Mack's incisive criticism of early Christian mythology and its influence on Western (specifically American) civilization. His cynical reading, which claims to take its cue from deconstruction, is assessed under three headings (which are inevitably interrelated): (1) The evangelical meaning of Jesus' death: the victimization of Jews; (2) The apocalyptic myth as social nightmare: the collusion of innocence and power, and (3) From diverse origins to reduced end product and back: the decanonization of the Christian Bible as ethical necessity. As a programmatic sug-gestion of how Mack's contribution can be taken further, the essay concludes by juxtaposing Mack's myth criticism with that of a selection of scholars (Crossan, Voltaire) and Polish poets (Zagajewski, Szymborska), whose points of view may serve not only to corroborate, but especially, to critically refine Mack's perspective.